Menuju Sistem Pendidikan Global - Saputra, Ananta (Unisia, 2016)
Education closely relates to globalization, because it is impossible to ignore globalization process through which a global society will be formed. Parallel with this, Indonesia should reform its education process, focusing on the establishment of an education system which is comprehensive and flexible, in order for its graduates to function effectively in a democratic global social life. Therefore, the education should be designed as such that students can develop their natural potencies and creativities in a freedom, equal and responsible atmosphere. The education should also produces graduates who can conceive their society, together with various factors causing their successes or failures. One of alternatives that should be done is to develop a global-based education.